Optimizing Intelligence Conditioning of Batang Resort Police’s Unit III Satintelkam Towards Civilians Affected by the PLTU Building to Maintain Social Security and Order - Allandefit Rihando Danantasa (Advances in Police Science Research Journal, 2024)
Social security and order, known as kamtibmas, is a dynamic social condition which is one of the precondition that can affect national development. Keeping the social security and order is one of the Indonesian National Police’s main duties as the national apparatus by the assist of civil and by upholding the human rights. The social security and order disruption faced by the Batang Resort Police right now is a showdown by the civil affected by PLTU construction, which has been held 19 times from May 31 until October 6 2022. Batang Resort Police’s Unit III Satintelkam ideally can execute intelligence conditioning, so that the civil won’t be doing showdown anymore. However, the advantageous condition for Indonesian National Police to keep the social security and order hasn’t been reached yet. The results of the research by Author show that the intelligence conditioning by Batang Resort Police’s Unit III Satintelkam hasn’t executed optimally. It’s because of how monotonous the intelligence conditioning’s method used by the unit, which is done with constructive persuasive method and Darsani, the key person of Format Ungkapno, is the target. This is caused by lack of personnel’s number and capability. Besides, there is a surveillance car that is not utilized optimally. The problem can be solved by coordinating with Central Java Regional Police’s Ditintelkam for agent backups to assist the destructive persuasive intelligence conditioning under the operational control of Batang Resort Police’s Unit III Satintelkam leader. The intelligence conditioning aims to decrease civil’s trust to the Format Ungkapno’s key person, known as Darsani.